RE-ENVISAGING TEACHING PRACTICUM: FACTORS OF SCHOOL-UNIVERSITY PARTNERSHIP - Masood, Faiza; Behlol, Malik Ghulam (International Journal of Psychosocial Rehabilitation, 2020)
School-university partnership prominence all over the world for the successful pre-service teacher education program. This paper highlight supportive factors of re-envisaging school-university partnership, contributes to the preparation of prospective teachers, during teaching practicum. The basic purpose behind the school-university partnership includes bridging the theory-practice gap, facilitating prospective teachers, and creating a cooperative atmosphere between two stakeholders during teaching practicum. The quantitative approach was used to collect data, through five points Likert scale from participants. Data were collected from one female institution by applying the purposive sampling technique. Prospective teachers of third and fifth semesters and their co-operative teachers participate in the study. Findings point out factors that enhance prospective teachers' learning and engagement during teaching practicum, it also indicates different ways to strengthen partnerships to bridge the gap between theory and practice. The study concluded that all identified factors of the school-university partnership are imperative and provide a baseline for the practicum process to prepare prospective teachers. All these factors should be used in teaching practicum to bridge the gap between theory and practice.